Secret agents : life as a professional spy - Manley, Claudia B. (New York : Rosen Publishing Group, 2001)
This compelling new series for the middle school reader is designed to appeal to the thrill-seeker in all of us. Each book includes information about a different extreme career, with a focus on safety and training. Readers will learn what it takes to get into these professions and what to expect when embarking on one. These volumes also provide information on the exciting aspects of these extreme careers and highlight the possible dangers and risks involved. Colorful photographs and informative sidebars help to make these books an invaluable resource for those young readers looking for a thrilling and fun-filled profession.Who hasn't at one time watched a James Bond movie and dreamed of being a spy? This book covers fictional and real-life secret agents, as well as describes the sometimes exciting, but often mundane, work involved. This book will change your ideas of spying forever!
Keywords: Spies; Espionage -- Vocational guidance; Vocational guidance